(untitled) (Global Journal of Management and Business Research, 2021)
Behavioural Finance is an area that needs to be studied within the context of the Indian stock market to assist investors in making rational investment decisions. This study examines the existence of herding behaviour in the Indian stock market considering various determinants of herd formation such as rising and declining market conditions and extreme market situations. The study is based on 46 companies selected from NSE Nifty 50 index based on their trading period. The methodology applied to validate the presence of herd formation is Cross-Sectional Absolute Deviation (CSAD) method.